Evidence for a novel function of Awd in maintenance of genomic stability - Romani, Patrizia (Sci Rep, 2017)
The abnormal wing discs (awd) gene encodes the Drosophila homolog of NME1/NME2 metastasis suppressor genes. Awd acts in multiple tissues where its function is critical in establishing and maintaining epithelial integrity. Here, we analysed awd gene function in Drosophila epithelial cells using transgene-mediated RNA interference and genetic mosaic analysis. We show that awd knockdown in larval wing disc epithelium leads to chromosomal instability (CIN) and induces apoptosis mediated by activation of c-Jun N-terminal kinase. Forced maintenance of Awd depleted cells, by expressing the cell death inhibitor p35, downregulates atypical protein kinase C and DE-Cadherin. Consistent with their loss of cell polarity and enhanced level of matrix metalloproteinase 1, cells delaminate from wing disc epithelium. Furthermore, the DNA content profile of these cells indicates that they are aneuploid. Overall, our data demonstrate a novel function for awd in maintenance of genomic stability. Our results are consistent with other studies reporting that NME1 down-regulation induces CIN in human cell lines and suggest that Drosophila model could be successfully used to study in vivo the impact of NME/Awd - induced genomic instability on tumour development and metastasis formation.